The Consequences of Unfulfilled Desire in Kazuo Ishiguro’s The Remains of the Day: Lacan Psychoanalysis Study - Maulana Aden Saladin; Zuhrul Anam (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Desire often produces psychological conflict and identity crisis, especially when an individual’s sense of self depends on social ideals and hierarchical authority. Using Lacanian psychoanalytic register theory, this study examines the consequences of the unfulfilled desire of Stevens, the main character in The Remains of the Day by Kazuo Ishiguro. The study explores how Stevens’ desire is constructed through Imaginary identification with ideal figures such as his father, and structured within the Symbolic order of professionalism, dignity, and loyalty to Lord Darlington. This study analyses key narrative events, dialogues, and character reflections using a qualitative descriptive method and content analysis to reveal how Stevens’ identity is formed and sustained by external authority. The findings demonstrate that Stevens’ desire is shaped not by personal fulfilment but by external ideals that structure his Symbolic identity and behaviour. Regret then emerges as a consequence of the collapse of the Symbolic framework. Lacanian theory can conceptualize this moment as the gap between Stevens’ ideal and his actual life.